Pengungkapan Standar GRI Terhadap Kinerja Sosial dalam Penyusunan Laporan Keberlanjutan di Instansi Pemerintah Daerah : (Studi Kasus Pemerintah Kota Bandung) - Yusuf Bastiar; Syaiful Rahman Soenaria (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This study examines the disclosure of GRI Standards on sosial performance in the preparation of sustainability reports in Local Government Agencies. Through a special method of Action Research. This method is by requesting data from people who have the capacity in the Bandung City Government. The results showed that the GRI 2021 Standards that have been included in the Bandung City government's sustainability report regarding general disclosures and material topics as well as specific disclosures regarding the impact of sosial aspects. In the sosial aspect, human rights are not violated and there are no cases or complaints to the Bandung City Government regarding human rights issues. In the human rights aspect, with various policies and programs established, such as strengthening human rights protection institutions, training for law enforcement officers, as well as advocacy and community education, the Bandung City Government seeks to ensure that the basic rights of every individual are respected and protected. The Bandung City Government has not yet produced a sustainability report that uses the comprehensive option based on GRI Standards 2021.